The Berenstain Bear Scouts and the search for Naughty Ned - Berenstain, Stan, 1923-; Berenstain, Jan, 1923-; Berenstain, Michael (New York : Scholastic, 1998)
When Naughty Ned becomes separated from his parents at Big Fun Park, Brother and Sister Bear take time out from their fun to search for him.
"Ages 6-10"--cover p. [4].
Keywords: Bears -- Fiction; Amusement parks -- Fiction; Scouts and scouting -- Fiction; Mystery and detective stories